2011
DOI: 10.1143/jpsj.80.013710
|View full text |Cite
|
Sign up to set email alerts
|

Possible Three-Dimensional Nodes in thes± Superconducting Gap of BaFe2(As1-xPx)2

Abstract: We theoretically examine the superconducting state of BaFe 2 (As 1Àx P x ) 2 , an isovalent doping 122-iron-pnictide superconductor. We construct a three-dimensional 10-orbital model by first-principles band calculation, and investigate the superconducting gap within the spin-fluctuation-mediated pairing mechanism. The gap is basically sAE, where the gap changes its sign between electron and hole Fermi surfaces, but three-dimensional nodal structures appear in the largely warped hole Fermi surface having a str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

22
126
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(149 citation statements)
references
References 41 publications
22
126
1
Order By: Relevance
“…The nodal superconductivity in these P-doped compounds is very striking, which raises the puzzling questions of whether, and why, the P doping is unique among iron-based superconductors. Although various theoretical explanations have been offered for this puzzle, investigators are far from reaching consensus [21][22][23][24][25].A recent empirical proposal is that the nodal state in ironpnictide superconductors, except for KFe 2 As 2 , is induced when the pnictogen height h Pn from the iron plane decreases below a threshold value of approximately 1:33 A [20]. According to this proposal, there may exist a transition from nodal to nodeless state as h Pn is tuned, for example, in underdoped BaFe 2 ðAs 1Àx P x Þ 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The nodal superconductivity in these P-doped compounds is very striking, which raises the puzzling questions of whether, and why, the P doping is unique among iron-based superconductors. Although various theoretical explanations have been offered for this puzzle, investigators are far from reaching consensus [21][22][23][24][25].A recent empirical proposal is that the nodal state in ironpnictide superconductors, except for KFe 2 As 2 , is induced when the pnictogen height h Pn from the iron plane decreases below a threshold value of approximately 1:33 A [20]. According to this proposal, there may exist a transition from nodal to nodeless state as h Pn is tuned, for example, in underdoped BaFe 2 ðAs 1Àx P x Þ 2 .…”
mentioning
confidence: 99%
“…The nodal superconductivity in these P-doped compounds is very striking, which raises the puzzling questions of whether, and why, the P doping is unique among iron-based superconductors. Although various theoretical explanations have been offered for this puzzle, investigators are far from reaching consensus [21][22][23][24][25].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5, 6) Furthermore, the study of angle-resolved photoemission spectroscopy (ARPES) 7) demonstrated that the observed FSs fulfill the nesting condition between the electron and hole FSs, which was consistent with the spin fluctuation theory in Ba122P. 8,9) From the crystallographic viewpoint, the appearance of SC would be ascribed to the optimization of the pnictogen (Pn) height from the Fe layer (h Pn ) 10) or the Pn-Fe-Pn bond angle (α), 11) which was also explained by nesting-based theories. 9,12) On the other hand, according to the nesting scenario, the distance between neighboring Fe layers, which must be correlated with interlayer hybridization and thus with anisotropy, should have a distinct influence on antiferromagnetism (AFM) and SC.…”
mentioning
confidence: 61%